Knowledge, Attitudes and Practices of Mozambican Public Employees on the Prevention of Covid-19 - Jose Luis Sousa Manjate; Félix Salvador Chavane; Hélio Rogério Martins; Leonardo Lúcio Nhantumbo (Revista Produção e Desenvolvimento, 2020)
Objective: To analyze the level of knowledge, attitudes, and practices of Mozambican public employees on the prevention of COVID-19.